Evening class - Binchy, Maeve (New York : Dell, 1998)
Teacher Aidan Dunne, passed over for the principal's job, is instead offered a post as head of a new evening school where he somewhat assuages his dream of visiting Italy by offering classes in Italian and draws an assortment of students whose lives are all transformed by the vivacious instructor, Nora O'Donoghue.
Adult
Adult
Wilson's Fiction
School Library Journal
Library Journal
780
Keywords: Teachers -- Ireland -- Dublin -- Fiction; Italian language -- Study and teaching -- Fiction; Teachers -- Dublin (Ireland) -- Fiction; Italian language -- Study and teaching -- Fiction